KEANEKARAGAMAN FORAMINIFERA BENTIK TELUK BALIKPAPAN, PROVINSI KALIMANTAN TIMUR - WIDIANINGSIH, MASTUTI (Jurnal Biologi Udayana, 2017)
Balikpapan Bay is one of locations of sampling sediments for the study of benthic foraminifera. The objective of this research was to determine the diversity of benthic foraminifera at different depths at Balikpapan Bay, East Kalimantan. Samples was selected at  depth of 0-20 m, then divided into 4 depths, 0-5 m, 6-10 m, 11-15 m, and 16-20 m. A total of 1553 specimens were obtained from 66 species, 7 ordo, and 17 family. Asterorotalia trispinosa is a species with the highest of abundance, that followed by Rotalia sp.1, Rotalia sp.2, and Trichammina nana. The diversity index of each sampling point was different, 8 points have stable diversity, 11 moderate points, and 1 unstable point. This condition were influenced by depth, brightness, temperature, pH, turbidity, salinity, and DO at each sediment sampling point.